If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -61 = 7x + -6(-1x + -5) Reorder the terms: -61 = 7x + -6(-5 + -1x) -61 = 7x + (-5 * -6 + -1x * -6) -61 = 7x + (30 + 6x) Reorder the terms: -61 = 30 + 7x + 6x Combine like terms: 7x + 6x = 13x -61 = 30 + 13x Solving -61 = 30 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -61 + -13x = 30 + 13x + -13x Combine like terms: 13x + -13x = 0 -61 + -13x = 30 + 0 -61 + -13x = 30 Add '61' to each side of the equation. -61 + 61 + -13x = 30 + 61 Combine like terms: -61 + 61 = 0 0 + -13x = 30 + 61 -13x = 30 + 61 Combine like terms: 30 + 61 = 91 -13x = 91 Divide each side by '-13'. x = -7 Simplifying x = -7
| sin(2*x)*sin(6*x)=cos(x)*cos(3*x) | | -4x=12x+32 | | =9d-7d+3d+2 | | 12n=8n+4 | | 9w=543 | | 54=4x+2(2x+3) | | 20x-16-3x-48+48+2=6x+168 | | 0.1(x-7)=35 | | -7b-3=-3b | | -69=3x+4(-5x+4) | | 18x^2=107x+6 | | -x-3y=1 | | -6y=2y+4 | | -13+6x=-61 | | x^2+156x+459=0 | | -2y(3y-2)-y=-2(y-4) | | -6x-3(x-4)=-51 | | 4(x+4)=16 | | 10=4x-5(x-4) | | 2x+2=24-2y | | an=0+(n-1)6 | | 6*(4y-10)=8*(2y-7) | | -70=-4x-5(-2x+8) | | (2/5)+y=3 | | 3a+20=2a+26 | | 6.8(x-2)=-0.2x+28.4 | | 187=3x+7(4x-3-3) | | 2x^2+x^2=400 | | 3(7x+5)=120 | | 4b=2b+24 | | 3x^2+46x+49=0 | | 7x-17=3x+9 |